Extreme pulse dosing of 10 kHz spinal cord stimulation: how low can you go? - Gupta, Mayank; Reinert, Amy; West, C. O.; Province-Azalde, Rose; Bradley, Kerry (Frontiers in Pain Research, 2025)
BackgroundPulse dosing of high frequency spinal cord stimulation at 10 kHz (10 kHz SCS) may offer comparable clinical benefits as continuous 10 kHz SCS, but extreme pulse dosing (EPD) has not been studied.MethodsPatients using an implantable pulse generator (IPG) with 10 kHz SCS to treat chronic back or leg pain were enrolled. After baseline assessments, patients underwent “EPD titration” starting at an EPD setting of 3%. Patients who preferred the EPD tried progressively lower EPD settings (0.6%, 0.3%, 0.14%, 0.06%), each for 7–10 days, until reaching an EPD they did not prefer over that previously tried. Patients were then followed up for 3 months at their lowest preferred EPD. All study visits included assessment of adverse events and patient-reported outcomes, including the numeric rating score (NRS) for pain intensity, Patient Global Impression of Change (PGIC), Oswestry Disability Index (ODI), and the PROMIS-SF for sleep disturbance. Device charging information was uploaded from the IPG at each visit.ResultsEighteen patients completed testing (13 M/5 F; mean age, 61 years); 14 patients (78%) reporting a preferred EPD (at any setting) to standard 10 kHz SCS. Among 18 patients, the most common lowest preferred EPD was 0.14% (28%), followed by 0.06% (22%) and 3% (17%). All post-SCS pain scores were lower than pre-SCS pain scores (median NRS, 8.5 vs. 3.0; p = .004). For overall pain, NRS values did not vary significantly across timepoints after the pre-SCS period (median range, 3.0–4.0; p > .05). Similarly, patient satisfaction, PGIC, ODI, PCS, and PROMIS-SF scores for EPD did not vary significantly from those at baseline. Daily IPG recharge times were significantly shorter using the patient's lowest preferred EPD than at baseline (median minutes, 3.0 vs. 31.8; p = .0001).ConclusionsEPD 10 kHz SCS may offer the same pain relief and quality-of-life benefits as standard 10 kHz SCS, while reducing recharge requirements and potentially lowering the risk of therapy habituation.